Demonstration of femtosecond broadband X-rays from laser wakefield acceleration as a source for pump-probe X-ray absorption studies - Behm,K; Hussein,AE; Zhao,TZ; Baggott,RA; Cole,JM; Hill,E; Krushelnick,K; Maksimchuk,A; Nees,J; Rose,SJ; Thomas,AGR; Watt,R; et al. (High Energy Density Physics, 2020)
We present X-ray absorption measurements near the K-edge of laser heated aluminum in a pump-probe configuration using X-rays generated in a laser wakefield accelerator. A 30 fs duration laser pulse from the Herculeslaser system was split into two beamlines, with one used to heat a 4µm thickness Al foil and the second to drive a laser wakefield accelerator. The laser-heated plasma was probed at various pump-probe delays using the femtosecond duration X-rays generated by betatron oscillations of the electrons in the wakefield. We observe an apparent blue-shift of the K-edge occurring on a sub-picosecond timescale in the transmission spectra.